Development of a method for quantifying relative importance of NPP cyber attack probability variables based on factor analysis and AHP. (15th December 2020) - Kim, Yong Sik; Choi, Moon Kyoung; Han, Sang Min; Lee, Chanyoung; Seong, Poong Hyun
Highlights: A necessity of following cyber security controls in order of priority for efficiency. Investigation and classification of the cyber attack probability variables for NPPs. Quantifying the relative importance of NPP cyber attack probability variables by using FA and AHP. Identification of Korean cyber security controls that have higher priority to be implemented. Abstract: The cyber security of NPPs recently has become a major issue, and a utility in Korea is requested to follow cyber security controls and to perform cyber security risk management based on the regulatory guide RS-015. Since it is difficult to fully implement the controls with limited resources, it is necessary to find which controls are relatively more important than other controls. The aim of this study is to develop a method for quantifying the relative importance of NPP cyber attack probability variables. These variables were investigated, and rearrangement and classification of them was validated by the factor analysis method. The relative importance among the variables was quantified by the AHP method. By applying the relative importance to the regulatory guide, the controls that have higher priority to be implemented were identified. Considering the relatively more important controls, it is expected that the utility can follow cyber security controls efficiently.